Le football professionnel en Europe est-il en crise ? Une réponse régulationniste - Jérémie Bastien (Revue de la Régulation)
From researchers’ point of view, the European professional football needs regulation because it is in financial crisis. That means it requires more regulatory measures to control clubs, as in the North American sports. However, the concept of regulation is more than the sole regulation in the French Régulation theory. In this way, this article identifies a regulation process which highlights the football reproductive capacity over time and in its current form. Thanks to institutional arrangements at the supranational and national levels, the clubs have the opportunity to accumulate deficits and debts. They are regularities. In view of the specificity of football meso-economics dynamics, the paper proposes a new reading of the financial crisis of professional football in Europe.